Comment on the ILC Draft Conclusions on Subsequent Agreements and Subsequent Practice in Relation to the Interpretation of Treaties - Kozłowski, Artur (Polish Review of International and European Law, 2021)
In 2018, the ILC completed its work on the Draft conclusions on subsequent agreements and subsequent practice in relation to the interpretation of treaties. There is still the dilemma of whether interpretation in its essence reflects more the assumptions of art or science. From this perspective, the ILC’s undertaking is the next step in the field of treaty interpretation that should provoke a moment of reflection and intellectual curiosity. Especially when the presented approach is the result of thorough research, is of a multilayered nature and consciously constitutes an element of a broader whole, and demonstrates the undeniable theoretical and practical value. The International Law Commission, in its final outcome on subsequent agreements and practice in relation to the interpretation of treaties, has obtained such a harmonized picture. This is the product of several factors. First, the proposals are of rich normative value. Their shape facilitates the potential defense of this normativity in the event of a dispute. Secondly, the draft skillfully combines the themes of lex generalis and lex specialis, situating deliberations in the correct systemic context, thus making the final result of the effort realistic. The notion of acquiescence, the unformalized nature of international law or the objectification of particular institutions of international law can be cited here as an example. As a consequence, thirdly, the ILC’s view of subsequent agreements and practice as essential elements of the treaty interpretation process is flexible and multidimensional.